Self-compassion moderates the relationship between neuroticism and depression in junior high school students - Wang, Ting; Wu, Xicong (Frontiers in Psychology, 2024)
Neuroticism is an emotion-related personality trait that is prone to depression. Self-compassion refers to an individual who treats himself in a peaceful, mindful and friendly way in the face of failure or frustration. The present study explored the relationship between neuroticism and depression in junior high school students and the moderating role of self-compassion. 757 junior high school students were surveyed by the Children' s Depression Inventory, Eysenck personality questionnaire short scale for Chinese and Chinese version of Self-compassion Scale. Results showed that Neuroticism positively predicted depression; Self-compassion has a significant moderating effect on neuroticism and depression. The higher the level of selfcompassion, the less neuroticism predicted depression. This indicated that selfcompassion interventions should be applied to students with neuroticism.